2019
DOI: 10.1057/s41270-019-00052-9
|View full text |Cite
|
Sign up to set email alerts
|

Review of a proposed methodology for bibliometric and visualization analyses for organizations: application to the collaboration economy

Abstract: This paper presents the bibliometric and visualization method applied to a dataset of 729 documents published in the collaborative economy research field. Four steps are described in details: 1) the delimitation of the field of study; 2) the selection of databases, keywords and search criteria; 3) the extraction, cleaning and formatting, and finally; 4) the co-citation analysis and visualization. The method validation section shows the results obtained by applying our methodological procedure to an author netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…According to van Eck and Waltman [ 29 ], co-citation analysis has no standard set of thresholds. However, Ertz et al [ 46 ] concluded that meaningful clusters were best visualized when established at a threshold of 20. Therefore, the selected cut-off point in this review was 20.…”
Section: Resultsmentioning
confidence: 99%
“…According to van Eck and Waltman [ 29 ], co-citation analysis has no standard set of thresholds. However, Ertz et al [ 46 ] concluded that meaningful clusters were best visualized when established at a threshold of 20. Therefore, the selected cut-off point in this review was 20.…”
Section: Resultsmentioning
confidence: 99%
“…Bibliometrics is a quantitative evaluation of publication and citation data [52], now used in almost all scientific fields to evaluate growth [53,54], maturity [55,56], leading authors [57,58], conceptual and intellectual maps [59,60], and a scientific community's trends and future agenda [61]. In social sciences, a large number of bibliometric studies related to different areas of knowledge, such as economics [62,63], finance [64,65], management, and business [66][67][68], among others, have been conducted.…”
Section: Methodsmentioning
confidence: 99%
“…We chose VosViewer instead of any other so ware because, unlike other programs that are normally used for bibliometric mapping (such as SPSS and Pajek), VosViewer focuses on the graphic representation of bibliometric maps, presenting these in a manner that is easy to interpret (Van Eck and Waltman, 2010). is so ware's use in studies related to the sharing economy eld may be observed in the systematic review recently conducted by Sainaghi et al (2020), as well as in the methodology proposed by Ertz and Leblanc-Proulx (2019), which is based on the collaboration economy.…”
Section: Methodsmentioning
confidence: 99%